Surgical treatment of inguinal hernias in children: review of methods and outcomes - S. S. Khilko; M. Yu. Morozova (Исследования и практика в медицине)
Inguinal hernias in children are one of the most common surgical diseases that occur mainly at an early age. The lack of proper treatment can lead to serious complications requiring emergency surgery. Modern treatment approaches make it possible to minimize these risks through the introduction of minimally invasive methods that take into account the anatomical and physiological characteristics of children.Purpose of the study. The aim was to analyze the literature data on the methods of surgical treatment and postoperative management of children with inguinal hernias, as well as to substantiate modern approaches focused on the age and anatomical and physiological characteristics of patients.Materials and methods. A systematic search and analysis of the results of publications and online resources for the period from 2019 to 2024 was carried out. All publications were indexed in the PubMed, e Library, Scholar, and CyberLeninka databases.  The search was carried out by keywords: "surgical treatment of inguinal hernias in children", "congenital inguinal hernia", "laparoscopic hernioplasty in children". The following criteria were applied to exclude irrelevant publications: the exclusion of duplicate data from different sources, as well as the exclusion of work related to the correction of inguinal hernias in the adult population. Results. Minimally invasive treatments such as LASSO (Laparoscopically Assisted Simple Suturing Obliteration) and SEAL (Subcutaneous Endoscopic Assisted Ligation) show the best results, including minimal duration of operations, low complication rate and short period of hospitalization. The PIRS (Percutaneous Internal Ring Suturing) method is also effective, although it is inferior to LASSO and SEAL. The LPEC (Laparoscopic Percutaneous Extraperitoneal Closure) technique has average performance. The Duhamel-1 and Duhamel-2 methods are characterized by a high duration of operations, long hospitalization, and a higher incidence of complications.Conclusion. Minimally invasive methods, especially LASSO and SEAL, are preferred due to their high efficiency and safety. The Duhamel-1 and Duhamel-2 methods are significantly inferior to modern approaches but remain relevant due to their simplicity and lack of need for special equipment.